Development of microsatellite markers in Qualea grandiflora (Vochysiaceae) and transferability to congeneric species, typical trees of the Brazilian savanna - Buzatti, Renata Santiago de Oliveira; Lemos-Filho, José Pires de; Lovato, Maria Bernadete (Biochemical systematics and ecology, 2014)
This study aimed to isolate and characterize microsatellite markers for Qualea grandiflora and to test their transferability to congeneric species Qualea multiflora and Qualea parviflora. These three species are widespread in the Cerrado, the largest, richest and probably the most threatened tropical savanna in the world. We characterized ten markers in 40 individuals belonging to two populations of Q. grandiflora and eight markers in 20 individuals belonging to one population of Q. multiflora and Q. parviflora. In Q. grandiflora, considering all 40 analyzed individuals, the number of alleles per locus ranged from eight to 21, and the average was 11.60. The mean number of alleles per locus was 8.8 and 7.3 in each population. The observed and expected heterozygosities (Ho and He) within populations varied from 0.235 to 0.944 and from 0.225 to 0.932, respectively. In Q. multiflora the number of alleles varied from two to 11 with an average of 5.75; the Ho ranged from 0.150 to 0.950, while He ranged from 0.191 to 0.817. In Q. parviflora, considering the seven polymorphic loci, the number of alleles ranged from two to 13, with an average of 7.5, while Ho ranged from 0.211 to 0.944, and He ranged from 0.193 to 0.906. The polymorphism level of the microsatellite markers here described enable them as powerful tools for future population genetic studies in these species, helping to answer ecological and evolutionary questions. •Ten polymorphic microsatellite markers were isolated in Qualea grandiflora.•Transferability of SSR markers was successful in Q. multiflora and Q. parviflora.•At least seven SSR markers were polymorphic in Q. multiflora and Q. parviflora.•These markers are valuable tools for population genetic studies in these species.•These markers can be used in kinship and paternity studies.